Gender Differences in Perceived Stress and Its Relationship to Telomere Length in Costa Rican Adults - Méndez-Chacón, Ericka (Frontiers in Psychology, 2022)
Introduction: Stress is associated with disease and reduced leukocyte telomere length (LTL). The objective of this research is to determine if self-perceived stress is associated with telomere length in Costa Rican adults and the gender differences in this association. Findings may help explain how some populations in apparent socioeconomic disadvantage and with limited access to specialized medical services have a remarkably high life expectancy. Methodology: Data come from the pre-retirement cohort of the Costa Rican Longevity and Healthy Aging Study (CRELES), a population based survey conducted in the households to 2327 adults aged 53 to 66 years. The DNA to measure LTL was extracted from blood cells in laboratories of the University of Costa Rica whereas the Blackburn laboratory at the University of California performed the telomere length measurement applying the quantitative polymerase chain reaction (Q-PCR). The relationship between telomere length and perceived stress was measured using least-squares multiple regression. Perceived stress was measured by a set of questions about family, job, finances and, health reasons to be stressed. Models included the control variables: 1) age and sex of the participant, 2) whether he or she resides in the Nicoya area, a “blue zone” known for its high longevity, and 3) the aforementioned sociodemographic, health and lifestyles characteristics. Results: Stress perception and LTL are significantly different by sex. Women perceived higher stress levels than men in almost all aspects studied, except work. Women have significantly longer telomeres. Shorter telomeres are significantly associated with caregiving stress in men and with parental health concerns in women. Counter-intuitive telomere lengthening were observed among women who feel stressed about caring for family members; and among men who feel stressed due to their family relationships as well as concerns about their own health. Discussion: Results confirm that people with self-perceived stress due to caregiving or health issues have shorter telomeres. The relationship between stress and telomere length differs between men and women. Gender relations exert a strong modifier effect on the relationship between stress and LTL: gender is related to perceived stress, telomere length, and apparently also to the way stress and LTL are related.